Childhood asthma and quality of life: insights from ICMH, Dhaka - Mahbubur Rahman, Mohammad; Fatema, Kanij; Abdur Rahman, Mohammad (International Journal of Contemporary Pediatrics, 2025)
Background: Asthma is a significant global health issue affecting both children and adults, negatively impacting various aspects of quality of life. In Bangladesh, one in thirteen children suffers from asthma, which hampers their daily activities. This study aimed to assess the health-related quality of life (HRQoL) in children with asthma. Methods: A descriptive cross-sectional study was conducted among 116 children with asthma, aged 7−17 years, at the Institute of Child and Mother Health, Matuail, Dhaka, Bangladesh in 2020. Data were collected using the Pediatric Asthma Quality of Life Questionnaire (PAQLQ) through direct interviews with children, supplemented with sociodemographic information and incomplete responses from parents. Statistical analysis was performed using SPSS version 26.0. Results: The overall PAQLQ score ranged from 2.48 to 6.52, with an average of 5.2. The greatest impairment was observed in the domain of 'Activity Limitation' (mean=3.6259), followed by 'Emotional Function' and 'Symptoms.' HRQoL decreased as asthma severity increased with age (r=-0.341, p=0.001). Uncontrolled asthma was associated with the lowest HRQoL scores (p=0.001) and a longer duration of suffering further impacted the PAQLQ score negatively. Conclusions: Childhood asthma significantly reduces quality of life, as indicated by statistical findings. PAQLQ can serve as a valuable tool for routine assessment in clinical practice. Training asthma educators at district and upazila-level hospitals could improve HRQoL evaluation and management for children with asthma in Bangladesh.